Utilization of Household Organic Waste As Solid Fertilizer With Maggot Black Soldier Fly (BSF) As A Degradation Agent - Deffi Ayu Puspito Sari; Richa Andreina; Prismita Nursetyowati1; Diki Surya Irawan; Aqil Azizi; Darmono Taniwiryono; Prima Hadi Putra (Faculty of Agriculture, Merdeka University Surabaya, Indonesia, 2022)
Household waste still becomes a national problem as it causes air, soil and water pollution and disturbs aesthetics. For this reason, comprehensive and integrated waste management from upstream to downstream needs to be carried out in order to provide economic and health benefits for the community and be safe for the environment. Organic waste processing can be performed using black soldier fly (BSF). BSF is a type of fly that can eat household organic waste, making this fly is widely used as an alternative to processing organic waste, especially from households. This research uses an experimental method of cultivation scale and produces a by-product in the form of solid fertilizer which then compared with the Decree of the Minister of Agriculture of the Republic of Indonesia No. 261 of 2019 concerning Organic Fertilizer, Biological Fertilizer and Soil Improvement. From laboratory tests, the parameters of C-organic, C/N, by-products, pH, macronutrients, heavy metals, micronutrients, and biological analysis met the quality standards.